INTENSITAS SERANGAN DAN KOMUNITAS RAYAP TANAH DI KECAMATAN CIKAMPEK - Ginuk Sumami; Agus Ismanto (Jurnal Penelitian Hasil Hutan, 1988)
The study was carried  out at Cikampek on three different soil types  namely  Red  Latosol,  Redish Brown Latosol  and Lateritie  Association; Complex of  Yellowish  Red Podzolic, Yellow  Podzolic  and  Regosol; Complex of Grumusol, Regosol and  Mediteran.Odontotermes  grandiceps Holmgren, Microtermes insperatus Kemner  and Macrotermes   gilvus (Hagen) seems  to  be common  species  in  the  above  locations. The  highest  density   was found on  Complex of  Yellowish  Red Podzolic, Yellow  Podzolic  and Regosol  (123  termites per  test  block), while   the  lowest  one  was found   on  Complex  of  Grumusol, Regosol  and Mediteran   (14  termites  per  test block). Termite attack intensity during  the  first,  second,  third  and fourth  period  of observation  in the three  soil types  were different.